Towards sustainable carbon markets: Requirements for ecologically effective, economically efficient, and socially just emissions trading schemes - Sven Rudolph; Christine Lenz; Achim Lerch; Barbara Volmert (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
Domestic climate policy emissions trading schemes appear to be spreading all over the word. However, carbon markets in existence often suffer from dilution in terms of ecological effectiveness, economic efficiency, and social justice. Thus, in order to firmly base carbon markets on the main pillars of Sustainable Development, this paper defines the criteria of ecological effectiveness, economic efficiency and social justice and operationalizes them for giving design recommendations for sustainable carbon markets. Methodologically, the paper uses welfare and institutional economics, jurisprudential reasoning, and modern climate justice thinking in order to discuss the three criteria. In addition, design and implication analysis is applied in order to develop design recommendations for sustainable carbon markets. By doing so, the paper provides evaluation criteria for emissions trading schemes in existence and in planning, but also allows for improvements in order to make emissions trading a valuable instrument of a sustainable global climate policy.
Keywords: D62; D63; Q48; Q54; Q58; 330; sustainability; emissions trading; climate policy; justice; efficiency; effectiveness; Emissionshandel; Nachhaltige Entwicklung; Klimaschutz; Allokationseffizienz; Wirkungsanalyse; Gerechtigkeit; Theorie